Afrykanika z kolekcji Aleksandra Wernera w zbiorach Muzeum Uniwersyteckiego w Toruniu - Baka-Theis, Małgorzata; Majoch, Sławomir (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2012)
Article presents African collection donated by Alexander Werner (1920–2011), polish painter, sculptor and graphic, to Nicolaus Copernicus University in 2004. Werner lived in London since the end of II World War, when he created the rest of his life. All inheritance of the artist is University Museum in Toruń. The introduction outlines the memoir of the artist. The second part of the text is characteristic batch of African objects. The collection includes: sculpture of ivory from Kingdom of Benin (Fig. 1); wood and small figure Ibeji, “image of twins”, form the Yoruba people of Nigeria from the Ivory Coast; (fig. 2); two dolls Akua’ba – wooden ritual fertility dolls from Ghana of Ashanti people (Fig. 3–4); the Antelope headdress Mask “Chi-wara” of thr Bamana people of Mali (Fig. 5); miniature “Passport Mask” whitch is a small portrait human face of Baule People (Fig. 6); paintedgourds Turkana Tribe of Norden Kenya, headrest Kambatta people of Ethiopia (Fig. 7) as well as five of pottery from North Africa.